World Tribology Congress III, Volume 2 2005
DOI: 10.1115/wtc2005-63355
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Lubricated Friction Experiments With Coarse Surface Texture

Abstract: Low-speed friction experiments were conducted under boundary lubrication in a pin-on-disk tester. The 304 stainless steel disk had smooth areas alternating with areas of coarse surface texture consisting of indents or macroscopic grooves, 0.3–0.4 mm in size and in area fractions varying between 25 and 70%. The 3.2 mm flat pin was also SS304. The coarse texture has detrimental effects. For each pattern the friction coefficient is greater than for the smooth areas. It becomes independent of load as boundary cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Dimple density, dimple width and depth, texture array and dimple shapes/orientation are major parameters for designing of texture patterns. For many research concerning the effect of those parameters, the results are inconclusive [38][39][40][41]. Studies showed that dimple density plays a vital role and it was suggested that 20 %-40 % of density can generate maximised hydrodynamic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Dimple density, dimple width and depth, texture array and dimple shapes/orientation are major parameters for designing of texture patterns. For many research concerning the effect of those parameters, the results are inconclusive [38][39][40][41]. Studies showed that dimple density plays a vital role and it was suggested that 20 %-40 % of density can generate maximised hydrodynamic pressure.…”
Section: Discussionmentioning
confidence: 99%